A comprehensive bioinformatic analysis of hepatitis D virus full‐length genomes. Issue 7 (21st February 2018) - Delfino, C. M.; Cerrudo, C. S.; Biglione, M.; Oubiña, J. R.; Ghiringhelli, P. D.; Mathet, V. L.
Summary: In association with hepatitis B virus (HBV), hepatitis delta virus (HDV) is a subviral agent that may promote severe acute and chronic forms of liver disease. Based on the percentage of nucleotide identity of the genome, HDV was initially classified into three genotypes. However, since 2006, the original classification has been further expanded into eight clades/genotypes. The intergenotype divergence may be as high as 35%‐40% over the entire RNA genome, whereas sequence heterogeneity among the isolates of a given genotype is <20%; furthermore, HDV recombinants have been clearly demonstrated. The genetic diversity of HDV is related to the geographic origin of the isolates. This study shows the first comprehensive bioinformatic analysis of the complete available set of HDV sequences, using both nucleotide and protein phylogenies (based on an evolutionary model selection, gamma distribution estimation, tree inference and phylogenetic distance estimation), protein composition analysis and comparison (based on the presence of invariant residues, molecular signatures, amino acid frequencies and mono‐ and di‐amino acid compositional distances), as well as amino acid changes in sequence evolution. Taking into account the congruent and consistent results of both nucleotide and amino acid analyses of GenBank available sequences (recorded as of January, 2017), we propose that the eight hepatitis D virus genotypes may be grouped into three large genogroups fully supported by their shared characteristics.